Activity concentration and transfer factors of natural and artificial radionuclides in the Swedish counties of Uppsala and Jämtland - Pallavicini, Nicola (SLU/Dept. of Soil and Environment, 2011)
The study was performed in two areas of Sweden respectively with high natural radioactivity background (County of Jämtland), and high 137Cs deposition area deriving from Chernobyl fallout (County of Uppsala.